Chronic obstructive pulmonary disease: hospital and intensive care unit outcomes in the Kingdom of Saudi Arabia - Alaithan, Abdulsalam M (Dove Medical Press, 2012)
BACKGROUND: There is little data surrounding the survival of patients with chronic obstructive pulmonary disease (COPD) who are admitted to the critical care unit with exacerbation of symptoms. We conducted a study to measure the in-hospital and intensive care unit (ICU) outcomes of patients admitted with COPD exacerbation, and identified the related prognostic factors. METHOD: We performed a retrospective cohort study of patients who were admitted to the adult ICU between January 2006 and July 2011 for COPD exacerbation in King Abdulaziz National Guard Hospital, Al-Hasa, Saudi Arabia. RESULTS: During the study period, a total of 119 patients were admitted to the ICU with acute respiratory failure attributed to COPD exacerbation. The mean age was 72 ± 13 years, and 44 (37%) were females. The main cause of respiratory failure was infection, which occurred in 102 (86%) patients. Thirty-nine (33%) of the admitted patients were mechanically ventilated, and the median duration was 2.6 (1–42) days. The median lengths of the ICU and hospital stays were 3 (1–40) and 9 (2–43) days, respectively. The ICU mortality was 6%, and hospital mortality was 11%. Low Glasgow Coma Scale on admission, intubation, duration of mechanical ventilation, current smoking, tracheostomy, cardiopulmonary arrest, and the development of acute renal failure were associated with higher hospital mortality. CONCLUSION: Early ICU and hospital mortality is low for COPD patients who have been admitted to the ICU with exacerbation. Low Glasgow Coma Scale scores on admission, intubation, prolonged use of mechanical ventilation, and the development of acute renal failure were identified as risk factors associated with increased hospital mortality.